1969
DOI: 10.1111/j.1365-2141.1969.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Activated Factor X with Di:isopropyl Fluorophosphate

Abstract: Summary. The esterase and coagulant activities of activated Factor X have been inhibited by radioactive di:isopropyl fluorophosphate. The amino acid sequence about the site of binding of the di:isopropyl moiety has been shown to be gly.asp.ser‐P‐gly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…It is not possible, however, to specify exactly the details of the mechanism. DFP is an irreversible inhibitor that binds the serine hydtoxyl at the active site of certain proteases, including several clotting enzymes (13,18,20,35). SBTI is also a serine protease inhibitor, but of a more specific nature.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible, however, to specify exactly the details of the mechanism. DFP is an irreversible inhibitor that binds the serine hydtoxyl at the active site of certain proteases, including several clotting enzymes (13,18,20,35). SBTI is also a serine protease inhibitor, but of a more specific nature.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Factor X is a serine protease [28,46,55] capable of hydrolyzing Arg-X peptide bonds (see below) and N-substituted esters of arginine. Although few detailed studies on the hydrolysis of synthetic substrates by Factor Xa have been reported, the limited data available indicate that arginine esters are greatly preferred over lysine esters and that a small residue on the arginine α-amino group, such as an acetyl substituent, provides a better substrate than larger aromatic substituents such as benzoyl or tosyl ( Table 5).…”
Section: Substrate Specificity Of Factor Xamentioning
confidence: 99%
“…As the recent reports on prothrombin activation indicate that the Arg-Thr bond is cleaved before the Arg-Ile [22], it is interesting to ask if this small sequence difference is responsible for this order of bond cleavage in prothrombin. Activated Factor X can be inhibited by diisopropylfluorophosphate (iPr 2 P-F) [46,55], phenylmethanesulfonyl fluoride (PMSF) [46] and by soybean trypsin inhibitor [8,56,66]. Factor Xa apparently is not inhibited by the lima bean trypsin inhibitor [43].…”
Section: Substrate Specificity Of Factor Xamentioning
confidence: 99%
“…§1734 solely to indicate this fact. iPr2P-F-inactivated factor Xa was prepared by incubating 1.0 mg of factor Xa, prepared as above, in 25 mM Tris'HCl buffer (pH 8.0) with 15 mM iPr2P-F in a total volume of 0.5 ml for 2.5 hr at 370C as described by Leveson and Esnouf (10). Treatment of factor Xa by iPr2P-F does not result in total loss of activity, but under these conditions we found that factor Xa lost >85% of its original activity.…”
mentioning
confidence: 99%